Cooperation between liver-specific mutations of pten and tp53 genetically induces hepatocarcinogenesis in zebrafish - Juanjuan Luo; Chunjiao Lu; Meilan Feng; Lu Dai; Maya Wang; Yang Qiu; Huilu Zheng; Yao Liu; Li Li; Bo Tang; Chuan Xu; Yajun Wang; et al. (Journal of Experimental & Clinical Cancer Research, 2021)
Abstract Background Liver cancer, mainly hepatocellular carcinoma, is one of the deadliest cancers worldwide and has a poor prognosis due to insufficient understanding of hepatocarcinogenesis. Previous studies have revealed that the mutations in PTEN and TP53 are the two most common genetic events in hepatocarcinogenesis. Here, we illustrated the crosstalk between aberrant Pten and Tp53 pathways during hepatocarcinogenesis in zebrafish. Methods We used the CRISPR/Cas9 system to establish several transgenic zebrafish lines with single or double tissue-specific mutations of pten and tp53 to genetically induce liver tumorigenesis. Next, the morphological and histological determination were performed to investigate the roles of Pten and Tp53 signalling pathways in hepatocarcinogenesis in zebrafish. Results We demonstrated that Pten loss alone induces hepatocarcinogenesis with only low efficiency, whereas single mutation of tp53 failed to induce tumour formation in liver tissue in zebrafish. Moreover, zebrafish with double mutations of pten and tp53 exhibits a much higher tumour incidence, higher-grade histology, and a shorter survival time than single-mutant zebrafish, indicating that these two signalling pathways play important roles in dynamic biological events critical for the initiation and progression of hepatocarcinogenesis in zebrafish. Further histological and pathological analyses showed significant similarity between the tumours generated from liver tissues of zebrafish and humans. Furthermore, the treatment with MK-2206, a specific Akt inhibitor, effectively suppressed hepatocarcinogenesis in zebrafish. Conclusion Our findings will offer a preclinical animal model for genetically investigating hepatocarcinogenesis and provide a useful platform for high-throughput anticancer drug screening.